Agroforestry and Management of Trees in Bunya County, Mayuge District, Uganda - Monica Kyarikunda; Antonia Nyamukuru; Daniel Mulindwa; John R. S. Tabuti (International Journal of Forestry Research)
Woody plant resources continue to disappear in anthropogenic landscapes in Uganda. To slow down further loss of these resources requires the collaboration of farmers in tree planting in agroforestry systems. Tree planting interventions with the collaboration of farmers require a good understanding of tree management practices as well as trees that best satisfy farmers’ needs. We carried out this research to determine (1) the most preferred tree species and reasons why they are preferred, (2) the species conservation statuses, and (3) existing tree management practices and challenges to tree planting. Fourteen priority species valued because they yield edible fruits and timber have been prioritised in this study. Farmers are interested in managing trees but are constrained by many factors, key among which is scarcity of land and financial capital to manage tree planting. Trees are managed in crop fields and around the homestead. From farmers’ reports, the highly valued species are increasing in the landscape. In conclusion, the potential to manage trees in agroforestry systems exists but is hampered by many challenges. Secondly, the liking of trees that supply edible fruits seems to support the welfare maximisation theory which ideally states that rural people manage trees with the aim of having regular access to products that satisfy their household needs and not for income generation.